2009
DOI: 10.1007/s11255-009-9650-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of abnormal renal cortical scintigraphy in children with first urinary tract infection: the importance of time factor

Abstract: TDT ≥ 48 h, TRT ≥ 24 h, axillary temperature ≥ 39°C, LC ≥ 13500 mm(-3), and age ≥ 18 months predicted abnormal DMSA scan in patients with first episode of UTI. Considerably higher TDT and TRT values of the current study compared to previous ones suggests the more important role of time factor in predicting abnormal DMSA findings in a developing country than in developed ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Because of high inflammatory markers and renal parenchymal involvement in the DMSA scan we assigned these infants to the APN group. Some authors demonstrated that renal parenchymal involvement in UTI is related to delayed treatment and longer duration of fever before antibiotic treatment [8, 13, 30, 43]. In our study fever ≥ 38°C was present significantly more often and duration of fever before antibiotic treatment was significantly longer in the group with APN compared to the lower UTI group.…”
Section: Discussionsupporting
confidence: 55%
“…Because of high inflammatory markers and renal parenchymal involvement in the DMSA scan we assigned these infants to the APN group. Some authors demonstrated that renal parenchymal involvement in UTI is related to delayed treatment and longer duration of fever before antibiotic treatment [8, 13, 30, 43]. In our study fever ≥ 38°C was present significantly more often and duration of fever before antibiotic treatment was significantly longer in the group with APN compared to the lower UTI group.…”
Section: Discussionsupporting
confidence: 55%
“…However, some reports have indicated that CRP levels have low Sp for detecting true APN. 9 10 Ansari Gilani, et al 11 reported in their study that CRP levels were not predictive of true APN in patients experiencing their first episode of a UTI using MLRA, although CRP was found to be significant by univariate analysis (CRP cutoff value, ≥3 mg/dL). They reported that a therapeutic delay time ≥48 h, therapeutic response time ≥24 h, axillary temperature ≥39℃, leukocyte count ≥13500/mm 3 , and age ≥18 months were predictors of true APN.…”
Section: Discussionmentioning
confidence: 93%
“…Although there are no further previous data on the effect of FAT on repeat DMSA and the formation and severity of permanent renal lesions, there are three studies on acute DMSA findings. According to Fernández-Menéndez et al and Ansari Gilani et al , children with abnormal acute phase DMSA were found to have an average FAT of 29.7 and 47.4 hours, respectively 9 10. Furthermore, when FAT was delayed by >24 hours, renal lesions in the acute DMSA were more common.…”
Section: Discussionmentioning
confidence: 98%
“…The importance of the duration of fever before treatment initiation (FBT) has been previously studied with controversial results 2 5 7–15. However, it is generally accepted that delaying treatment for over 48 or 72 hours can lead to acute renal lesions and consequent permanent renal lesions based on DMSA scintigraphy findings 9 10 13 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation